Real‐world outcomes with recombinant factor VIIa treatment of acute bleeds in haemophilia patients with inhibitors: results from the international ONE registry. (5th April 2013) - Chambost, H.; Santagostino, E.; Laffan, M.; Kavakli, K.; ,
Summary The ONE Registry (OR) was an international prospective observational study of on‐demand recombinant factor VIIa (rFVIIa) treatment for mild to moderate bleeds in haemophilia A/B patients with inhibitors. To describe real‐world use of single and multi dose rFVIIa and to compare outcomes, including effectiveness, safety, quality of life and treatment satisfaction associated with treatment. Baseline data included demographics, treatment, medical and bleed history and patient/caregiver‐reported outcomes regarding bleeds. rFVIIa was prescribed according to routine practice; regimens varied and initial dose was categorized as low (LD, ≤120 μg kg−1), intermediate (ID, >120 and <250 μg kg−1) or high (HD, ≥250 μg kg−1). OR included 102 patients and 85 (83%) reported 494 bleeds overall. Mean age was 23 years (SD 16.4), with 52% ≥18 years. Majority of bleeds (n = 350, 71%) involved ≥1 joints; 46% involved a target joint. Median initial dose was 90 μg kg−1 in LD (range 87–120, n = 156), 174 μg kg−1 in ID, (range 121–249, n = 127) and 270 μg kg−1 in HD, (range 250–375, n = 211). For spontaneous bleeds, effective haemostasis rate at 9 h was 63% LD, 60% ID and 56% HD. Rates of combined partially effective/effective haemostasis was 85% LD, 96% ID and 86% HD. Median number of doses in HD was one (range 1–7), compared with two in LD (range 1–17) and ID (range 1–23). No thromboembolic events were reported in 1145 doses given. These observational data in real life are consistent with previous studies which have shown similar overall effectiveness of rFVIIa and similar effectiveness and safety across different patterns of standard initial dosing.